2010
DOI: 10.4995/wrs.2010.7744
|View full text |Cite
|
Sign up to set email alerts
|

Flushing or doe relocation as biostimulation methods for improvement of sexual behaviour and performance of multiparous rabbit doe after a summer resting period

Abstract: ABSTRACT:A study was conducted to clarify the infl uence of fl ushing or doe relocation as biostimulation methods on oestrus response and subsequent performance on thirty NZW multiparous 10-11-month-old rabbit does after a twomonth resting period in summer. After weaning of their last litter in June, the does were not re-mated and were fed a 100 g daily ration till September, the end of resting period. Then the does were randomly allocated to three groups (10 does/group): a control group (C) in which does rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
4
1
1
Order By: Relevance
“…The KR (on average 70.1 %) was consequently 2.1 % lower. In the given analysis, the KR was also lower than that reported by Castellini et al (2010), Manal (2010), Gerencsér et al (2011), Coutelet (2015, and Theau-Clément et al (2016). Furthermore, the LS was relatively low compared with results from the literature concerning the breeding goals of modern hybrid rabbit strains (Coutelet, 2015;Maertens and Buys, 2015;Maertens and De Bie, 2017).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The KR (on average 70.1 %) was consequently 2.1 % lower. In the given analysis, the KR was also lower than that reported by Castellini et al (2010), Manal (2010), Gerencsér et al (2011), Coutelet (2015, and Theau-Clément et al (2016). Furthermore, the LS was relatively low compared with results from the literature concerning the breeding goals of modern hybrid rabbit strains (Coutelet, 2015;Maertens and Buys, 2015;Maertens and De Bie, 2017).…”
Section: Discussioncontrasting
confidence: 52%
“…Schüddemage (1999), Carluccio et al (2004) and Coutelet (2015) found respective pregnancy rates between 64 % and more than 80 % and an average LS of between 8.1 and 10.7 total kits born in different breeds. In practice, the KR is lower than the conception rate and varies widely between 29 % and 90 % (Dimitrova et al, 2009;Castellini et al, 2010;Manal, 2010;Gerencsér et al, 2011;Coutelet, 2015;Theau-Clément et al, 2016). It has been previously shown that housing and feeding are factors which influence reproductive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, previous works reported a direct correlation of oestradiol concentration in plasma with vulva color and receptivity of rabbit females (Ubilla and Rebollar, 1995, Rodriguez de Lara and Fallas, 1999and Manal, 2010. Our results also indicated that hormonal eCG treatment markedly (P<0.05) increased receptivity of females to 82% compared with 59% in control (data not shown) in a coincidence with significant increase in serum E 2 concentration (5.52 pg/ml for eCG vs 4.09 pg/ml for control, Figure 1).…”
Section: Discussionmentioning
confidence: 92%
“…The present results are in accord with Martınez-Paredes et al (2012), who recommended that the introduction of a short flushing around first AI is used for good fertility rates at the 1st parturition in multiparous rabbits. Increasing litter size of does in G2 (110% NRC) may be attributed to that a short flushing period of 7 days could be good bio-stimulation technique for oestrus synchronisation and development of receptivity in multiparous constrained fed multiparous NZW rabbit does after a long break period (Manal, 2010).…”
Section: The First Experiment: the Main Effects Of Dietary Level Of Lmentioning
confidence: 99%